Studies on Homalomeneae (Araceae) of Borneo XIX: Three new species of geologically obligated Homalomena from Sabah, Malaysian Borneo - Kartini, Saibeh; Boyce, P.C; Wong, Sin Yeng (BGBM Berlin-Dahlem, 2015)
Three new geologically obligated species of Homalomena Schott are described from Sabah, Malaysian Borneo. Rheophytic H. gempal Kartini, P. C. Boyce & S. Y. Wong, sp. nov., restricted to rhyolite, belongs to the Chamaecladon clade and is compared to H. atrox P. C. Boyce & al. and H. paucinervia Ridl. Homalomena marasmiella Kartini, P. C. Boyce & S. Y. Wong, sp. nov., restricted to ultramafic substrates, forms an apparently natural grouping with H. stella P. C. Boyce & S. Y. Wong and H. vagans P. C. Boyce, and together these are termed the Vagans Complex. Homalomena simunii Kartini, P. C. Boyce & S. Y. Wong, sp. nov. is the third species of the Insignis clade to be described from Sabah and is restricted to basalt. All three species are illustrated from living plants.